Magnetic fields in electrochemistry: The Lorentz force. A mini-review - MONZON, LORENA; COEY, JOHN (My University, 2014)
Some recent work on the flow induced by uniform or non-uniform magnetic fields acting on currents in an electrochemical cell is reviewed. The effects include modifying the structure and texture of electrodeposits including their chirality, controlling hydrogen bubble release, inducing microfluidic flow and influencing nucleation. Much of this depends on micro-magnetohydrodynamic flow, on a scale of microns.
PUBLISHED
Keywords: Electrodeposition; nucleation